Technology of teaching skills and self-learning activities of university students (Pedagogy of Higher and Secondary Education, 2012)
Sereginа I. Technology of teaching skills and self-learning activities of university students.The article deals with the technology of forming skills and self-control of studying activity of university students.
Keywords: self-control; ability and skills of self-control of students; technology of forming skills and self-control of studying activity of students